The effect of using the ice cream sticks strategy on the achievement of sixth grade female students in science (The Peerian Journal, 2025)
The research. aims to identify the effect. of using the ice cream sticks strategy. on the achievement of sixth. grade female students in science. This study was conducted. in Iraq. The research sample consisted of (60) female students. The other is a control and one with a post-test for achievement, and the researcher intentionally chose the research sample, which is the Sumer Elementary School for Girls. As for the research group, it was chosen by a simple random drawing method, and the two research groups were rewarded statistically. It is a multiple-choice type, and the apparent validity and validity of the content were verified for it. The stability of the achievement test items was found by two methods of midterm division and the internal consistency method. The researcher applied the experiment in the second semester (2022-2023). The results of the research showed the superiority of the experimental group students who studied according to the strategy of ice cream The students of the control group, who studied according to the usual method in the collection of science, and in the light of the results of the research, the researcher presented a set of conclusions, recommendations and suggestions.